Pengaruh Antara Literasi Keuangan, Pendidikan Ekonomi Keluarga, Dan Kontrol Diri Terhadap Pola Pengeluaran Siswa SMA - Brian Baghaskoro Putra Christanto; Eka Indah Nurlaili (Universitas Pakuan, 2026)
DESIGN OF AN EMPLOYEE ABSENCE SYSTEM USING WEBSITE-BASED GPS (CASE STUDY: PAHLAWAN PHARMACY) This study aims to analyze the influence of financial literacy, family economic education, and self-control on the spending patterns of students at Kalam Kudus Christian Senior High School Surabaya. The study is motivated by students' limited ability to manage pocket money wisely, reflected in impulsive buying behavior, low saving habits, and inadequate financial planning. This research employed a quantitative approach using an ex post facto causal-comparative design. The participants were students of Kalam Kudus Christian Senior High School Surabaya selected through probability sampling. Data were collected using validated and reliable questionnaires and analyzed through descriptive statistics, assumption testing, and multiple linear regression to examine both partial and simultaneous effects. The independent variables consisted of financial literacy, family economic education, and self-control, while spending pattern served as the dependent variable. The study is expected to demonstrate that financial literacy, family economic education, and self-control have positive and significant influences on students' spending patterns, both individually and simultaneously. The findings are expected to contribute to the development of economic education in schools, strengthen the family's role in financial socialization, and encourage more rational, responsible, and sustainable financial management behavior among adolescents in everyday life and future financial decision making.